Evaluation of a clinical method for selective electrode deactivation in cochlear implant programming - Warren, Sarah E.; Atcherson, Samuel R. (Frontiers in Human Neuroscience, 2023)
Background: Cochlear implants are a neural prosthesis used to restore the perception of hearing in individuals with severe-to-profound hearing loss by stimulating the auditory nerve with electrical current through a surgically implanted electrode array. The integrity of the interface between the implanted electrode array and the auditory nerve contributes to the variability in outcomes experienced by cochlear implant users. Strategies to identify and eliminate poorly encoding electrodes have been found to be effective in improving outcomes with the device, but application is limited in a clinical setting. Objective: The purpose of this study was to evaluate a clinical method used to identify and selectively deactivate CI electrodes related to poor electrode-neural interface. Methods: Thirteen adult CI users participated in a pitch ranking task to identify indiscriminate electrode pairs. Electrodes associated with indiscriminate pairs were selectively deactivated, creating an individualized experimental program. Speech perception was evaluated in the baseline condition and with the experimental program before and after an acclimation period. Participant preference responses were recorded at each visit. Results: Statistically significant improvements using the experimental program were found in at least one measure of speech perception at the individual level in four out of 13 participants when tested before acclimation. Following an acclimation period, ten out of 13 participants demonstrated statistically significant improvements in at least one measure of speech perception. Statistically significant improvements were found with the experimental program at the group level for both monosyllabic words (p=0.006) and sentences in noise (p=0.020). Additionally, ten participants preferred the experimental program prior to the acclimation period and eleven preferred the experimental program following the acclimation period. Conclusion: Results from this study suggest that electrode deactivation may yield improvement in speech perception following an acclimation period. A majority of CI users in our study reported a preference for the experimental program. This method proved to be a suitable clinical strategy for identifying and deactivating poorly encoding electrodes in adult CI users.